The impact of depression and anxiety on academic performance among university students in UAE: evaluating a CBT-based online intervention in academically struggling students with low mood - Awadalla, Suheir (2021)
Rising rates of university students experiencing symptoms of depression and anxiety have been observed, both of which affect cognitive function. While some studies suggest that depression can significantly impact and impair students’ academic performance, study satisfaction, and general well-being, the relationship between anxiety and academic outcomes is perhaps more complex.